Prognostic and predictive factors in deciding the use of chemotherapy for hormone receptor positive, Herceptin 2 negative breast cancer - Salman, Muhammad; Babar, Zaheer; Qandil, Naim; Macano, Christina (International Surgery Journal, 2025)
Women suffering from hormone receptor positive, Herceptin 2 receptor (HER2) negative and node negative early breast cancer (EBC) receive adjuvant endocrine treatment as part of systemic treatment. The need for adjuvant chemotherapy in this patient group, regarding treatment benefit, can be assessed using validity of prognostic and predictive factors. A review was performed to assess the clinical validity with controversies of predictive and prognostic factors in use of adjuvant chemotherapy in early breast cancer (EBC). The cost effectiveness and turnaround time of genomic test also discussed. Retrospective cohort studies ranging from 2009 to 2024 were searched. Primarily tumour stage is the most important prognostic indicator, along with patient factors, preference and performance status. Considering intermediate group of breast cancer T1b to T3 node negative, ER positive, HER2 negative, the recurrence score (RS) is used to guide the decision of adjuvant chemotherapy. Although RS is well validated, other assays may also be acceptable. Women with newly diagnosed EBC should undergo hormone receptor and HER2 overexpression testing. Gene expression studies have identified several distinct breast cancer subtypes that differ markedly in prognosis. Further studies on genomic data derived from breast cancer specimen is going on. The circulating tumour cells (CTCs), a non-invasive, liquid based prognostic marker along with other liquid biopsy techniques are awaiting clinical validity.